Secreted frizzled related protein 2 (Sfrp2) is the key Akt-mesenchymal stem cell-released paracrine factor mediating myocardial survival and repair - Mirotsou, Maria (National Academy of Sciences, 2007)
Stem cell therapy has emerged as a promising tool for the treatment of a variety of diseases. Previously, we have shown that Akt-modified mesenchymal stem cells mediate tissue repair through paracrine mechanisms. Using a comprehensive functional genomic strategy, we show that secreted frizzled related protein 2 (Sfrp2) is the key stem cell paracrine factor that mediates myocardial survival and repair after ischemic injury. Sfrp2 is known to modulate Wnt signaling, and we demonstrate that cardiomyocytes treated with secreted frizzled related protein increase cellular β-catenin and up-regulate expression of antiapoptotic genes. These findings reveal the key role played by Sfrp2 in mediating the paracrine effects of Akt-mesenchymal stem cells on tissue repair and identify modulation of Wnt signaling as a therapeutic target for heart disease.